2010
DOI: 10.1093/nar/gkq1206
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation of eIF4A by eIF4B and eIF4G

Abstract: eIF4A is a key component in eukaryotic translation initiation; however, it has not been clear how auxiliary factors like eIF4B and eIF4G stimulate eIF4A and how this contributes to the initiation process. Based on results from isothermal titration calorimetry, we propose a two-site model for eIF4A binding to an 83.5 kDa eIF4G fragment (eIF4G-MC), with a high- and a low-affinity site, having binding constants KD of ∼50 and ∼1000 nM, respectively. Small angle X-ray scattering analysis shows that the eIF4G-MC fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 46 publications
(74 reference statements)
11
85
0
Order By: Relevance
“…Moreover, eIF4G accelerates phosphate release and thereby RNA release. The scaffolding protein eIF4G may therefore act in a catalytic fashion, inducing multiple rounds of formation of eIF4A-eIF4B-RNA 92 , which would also be consistent with the structural and biochemical evidence (FIG. 4).…”
Section: Nuclear Specklessupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, eIF4G accelerates phosphate release and thereby RNA release. The scaffolding protein eIF4G may therefore act in a catalytic fashion, inducing multiple rounds of formation of eIF4A-eIF4B-RNA 92 , which would also be consistent with the structural and biochemical evidence (FIG. 4).…”
Section: Nuclear Specklessupporting
confidence: 85%
“…In addition, full-length eIF4G might also increase binding of eIF4A to RNA by providing additional RNAbinding sites 85 . A further study indicated that eIF4G promotes the formation of a complex of eIF4A, eIF4B and RNA 92 . Moreover, eIF4G accelerates phosphate release and thereby RNA release.…”
Section: Nuclear Specklesmentioning
confidence: 95%
See 2 more Smart Citations
“…This conclusion is supported by the finding that PDCD4 inhibits cap-dependent, but not cap-independent, mRNA translation (10,33). The RNA helicase activity of eIF4A is stimulated not only through its association with eIF4G, but also upon interaction with eIF4B (34,35). In part, the stimulation occurs through an eIF4B-induced enhancement of the affinity of eIF4A for both RNA and ATP.…”
Section: Discussionmentioning
confidence: 87%